Acceptance Level Analysis of SMEs Towards Financial Technology P2P Lending in Palembang South Sumatra - Sartika, Dewi; Zinaida, Rahma Santhi; Fitriyani, Rosha; Merdianto, Efran (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2025)
The emergence of financial technology (fintech) plays a strategic role in economic development, particularly in providing digital financing and payment services for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze MSME actors’ perceptions of perceived usefulness and perceived ease of use of peer-to-peer (P2P) lending systems, examine their level of trust, evaluate their attitudes toward P2P lending services, and assess their intention to use these services. A quantitative descriptive approach was employed with a sample of 300 MSME actors in Palembang City selected through purposive sampling. Data were collected using questionnaires distributed with the assistance of the Palembang City Office of Cooperatives and MSMEs and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that perceived usefulness significantly influences perceived ease of use but does not significantly affect trust. Perceived ease of use significantly affects trust, and trust significantly influences user attitudes. User attitudes, in turn, significantly affect MSME actors’ intention to use fintech P2P lending services. These findings indicate that psychological factors, particularly perceived ease of use and trust, are critical determinants in encouraging the continued use of fintech services, which may contribute to improved financial performance among MSME actors in Palembang City. Keywords: Perceived usefulness, Perceived ease of use, Trust, Attitude, Interest In User, Peer to peer lending Abstrak Kemunculan Financial Technology (fintech) dalam beberapa tahun terakhir memiliki peran strategis dalam pembangunan ekonomi, khususnya dalam penyediaan layanan pembiayaan dan pembayaran digital bagi Usaha Mikro, Kecil, dan Menengah (UMKM). Penelitian ini bertujuan menganalisis persepsi kegunaan dan kemudahan penggunaan layanan peer-to-peer (P2P) lending, tingkat kepercayaan, sikap pelaku UMKM, serta minat penggunaan layanan tersebut. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan sampel 300 pelaku UMKM di Kota Palembang yang dipilih melalui purposive sampling. Data dikumpulkan melalui kuesioner dengan bantuan Dinas Koperasi dan UMKM Kota Palembang dan dianalisis menggunakan Structural Equation Modeling–Partial Least Squares (SEM-PLS) dengan perangkat lunak AMOS. Hasil penelitian menunjukkan bahwa persepsi kegunaan berpengaruh signifikan terhadap persepsi kemudahan penggunaan, tetapi tidak berpengaruh signifikan terhadap kepercayaan. Persepsi kemudahan penggunaan berpengaruh signifikan terhadap kepercayaan, kepercayaan berpengaruh signifikan terhadap sikap pengguna, dan sikap pengguna berpengaruh signifikan terhadap minat penggunaan layanan P2P lending. Temuan ini menegaskan bahwa faktor psikologis, khususnya kemudahan penggunaan dan kepercayaan, merupakan determinan utama dalam mendorong minat penggunaan fintech yang berkelanjutan, yang berpotensi meningkatkan kinerja keuangan pelaku UMKM di Kota Palembang. Kata Kunci : Persepsi, kegunaan, kemudahan, kepercayaan, sikap, minat, pinjaman ·